HIT AND RUN: A Phenomenological Study of Producer Experience in e-Commerce Transactions with the Pre-Order System from a Fiqh Muamalah Perspective - Asnita, Dessy; Mudrika, Syarifah (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This research was conducted on clothing manufacturers located in Bandung and Bekasi, as well as on one distributor in Medan. The "hit & run" phenomenon in e-Commerce transactions with the Pre-Order (PO) system has a significant impact on the existence of sales and the operational business of manufacturers. In the Pre-Order model, buyers place orders for products but often fail to make payments or disappear after the goods are sewn. This phenomenon results in stock accumulation, disruption of financial flows, and financial losses for manufacturers. The objective of this study is to analyze the impact of the "hit & run" phenomenon on clothing manufacturers and to find solutions to address this issue. The research method used is a qualitative approach with a descriptive phenomenological type. Data was collected through interviews with eight clothing manufacturers experienced in PO transactions, using WhatsApp chats and Zoom Meetings. The research findings show that the "hit & run" phenomenon harms manufacturers and causes uncertainty in their business operations. The implications of this study highlight the importance of developing more cautious policies in accepting orders and implementing effective communication strategies to minimize the risk of losses. This research provides an in-depth understanding of the dynamics of e-Commerce transactions with the PO system and valuable insights for manufacturers in managing risks and improving their business continuity in a competitive market.